Teleworking: A Curse or a Blessing for Gender Equality and Work-Life Balance? - Manuela Tomei (Intereconomics, 2021)
Affordable, reliable and high-quality child and elderly care services are essential for employees to do teleworking in an efficient manner.
Keywords: 330; Telearbeit; Gleichberechtigung; Familie-Beruf